Carbon dioxide versus room air insufflation during balloon-assisted enteroscopy: A systematic review with meta-analysis - Shiani, Ashok; Lipka, Seth; Lai, Andrew; Rodriguez, Andrea C.; Andrade, Christian M.; Kumar, Ambuj; Brady, Patrick (Endoscopy International Open, 2017)
Background and study aims Carbon dioxide (CO2) insufflation has been suggested to be an ideal alternative to room air insufflation to reduce trapped air within the bowel lumen after balloon assisted enteroscopy (BAE). We performed a systematic review and meta-analysis to assess the safety and efficacy of utilizing CO2 insufflation as compared to room air during BAE. Patients and methods The primary outcome is mean change in visual analog scale (VAS; 10 cm) at 1, 3, and 6 hours to assess pain. Secondary outcomes include insertion depth (anterograde or retrograde), adverse events, total enteroscopy rate, diagnostic yield, mean anesthetic dosage, and PaCO2 at procedure completion. We searched MEDLINE and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception until May 2015. Multiple independent extractions were performed, the process was executed as per the standards of the Cochrane collaboration.Results Four randomized controlled trials (RCTs) were included in the meta-analysis. VAS at 6 hours favored CO2 over room air (MD 0.13; 95 % CI 0.01, 0.25; p = 0.03). Anterograde insertion depth (cm) was improved in the CO2 group (MD, 58.2; 95 % CI 17.17, 99.23; p = 0.005), with an improvement in total enteroscopy rate in the CO2 group (RR 1.91; 95 % CI 1.20, 3.06; p = 0.007). Mean dose of propofol (mg) favored CO2 compared to air (MD, – 70.53; 95 % CI – 115.07, – 25.98; P = 0.002). There were no differences in adverse events in either group.Conclusions Despite the ability of CO2 to improve insertion depth and decrease amount of anesthesia required, further randomized control trials are needed to determine the agent of choice for insufflation in balloon assisted enteroscopy.